2015
DOI: 10.1037/cap0000024
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of personality disorders and health outcomes.

Abstract: Personality disorders have been associated with a wide swath of adverse health outcomes and correspondingly high costs to healthcare systems. To date, however, there has not been a systematic review of the literature on health conditions among individuals with personality disorders. The primary aim of this article is to review research documenting the associations between personality disorders and health conditions. A systematic review of the literature revealed 78 unique empirical English-language peer-review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 106 publications
1
80
0
Order By: Relevance
“…The serving process of other-oriented volunteering stresses unselfishness, sharing, other-directedness, and generosity, which are counteractive to the ego-centric and self-serving culture that is upheld nowadays and may harm mental and behavioural health [23]. In fact, some personal intrinsic motives, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The serving process of other-oriented volunteering stresses unselfishness, sharing, other-directedness, and generosity, which are counteractive to the ego-centric and self-serving culture that is upheld nowadays and may harm mental and behavioural health [23]. In fact, some personal intrinsic motives, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review concerns the diagnostic comorbidity between borderline personality disorder (BPD) and the somatic symptom and related disorders or somatoform disorders as defined by the Diagnostic and Statistical Manual of Mental Disorders (DSM) (American Psychiatric Association (APA) , 1980, 1994, 2013). Historically, these disorders have been conceptualized as fairly distinct; however, similarities in their clinical presentation-including shared risk factors (early trauma, gender), correlates (emotion dysregulation, self-harm), chronic course, and consequences (functional impairment, significant healthcare utilization)warrant closer consideration of their overlap (van Dijke, 2012;Dixon-Gordon, Whalen, Layden, & Chapman, 2015;van der Kolk et al, 1996;Quirk et al, 2016;Sansone, Wiederman, & McLean, 2008). Previous narrative reviews on this topic were published over 20 years ago, including the association of personality traits and disorders with somatoform disorders (Bass & Murphy, 1995;Kirmayer, Robbins, & Paris, 1994), and a review of published case studies that examined the comorbidity of personality disorders with factitious disorder (Goldstein, 1998).…”
mentioning
confidence: 99%
“…A small but growing body of research suggests an association between BPD and a broad range of physical health problems (see Dixon-Gordon, Whalen, Layden, & Chapman, in press). For example, studies using large, representative community samples have found a unique association between BPD and numerous physical health conditions, including cardiovascular disease, hypertension/arteriosclerosis, hepatic disease, gastrointestinal disease, arthritis, and venereal disease (e.g., El-Gabalawy et al, 2010; Moran et al, 2007), as well as various chronic pain conditions (e.g., musculoskeletal pain, headache; Braden & Sullivan, 2008; McWilliams & Higgins, 2013).…”
mentioning
confidence: 99%